Effects of paclobutrazol concentrations and watering frequencies on the flowering ratio of cucumber plants (Cucumis sativus L.) - Ratih Hartono Putri; Aziz Purwantoro; Valentina Dwi Suci Handayani; Dyah Weny Respatie (Jurnal Ilmu Pertanian, 2022)
Generally, cucumber plants have more male flowers than female flowers. The fewer number of female flowers is one of the problems of cucumber production. Flowering regulation can be performed by applying growth regulators and water management. The study aims to determine the effects of paclobutrazol concentrations and watering frequencies on the flowering ratio of cucumber plants. The experiment was arranged in a factorial Randomized Completely Block Design at the Agricultural, Food, and Fishery Extension Center, Seyegan, Yogyakarta. The first factor was the paclobutrazol concentrations consisting of four levels (a control, 0.187 mL.L-1, 0.375 mL.L-1, and 0.562 mL.L-1). Meanwhile, the second factor was the watering frequency consisting of three levels (once a day, once every two days, and once every three days). The observed data were performed using the analysis of variance (ANOVA) and followed with Duncan’s Multiple Range Test at α= 5 %. The paclobutrazol concentrations resulted in a significant effect on all of the observed variables. Meanwhile, watering frequencies showed no significant effect on the male flowers, female flowers and ratio of male to female flowers in cucumber. There was an interaction effect of paclobutrazol concentration and watering frequency on the plant height and flowering age of cucumber plants. The treatment of paclobutrazol at a concentration of 0.375 mL.L-1, decreased of male flowers and increased of female flowers, reducing the ratio of male and female flowers of cucumber plants at various watering frequencies.-1